Estrogen receptor alpha mediates epithelial to mesenchymal transition, expression of specific matrix effectors and functional properties of breast cancer cells - Bouris, P.; Skandalis, S. S.; Piperigkou, Z.; Afratis, N.; Karamanou, K.; Aletras, A. J.; Moustakas, A.; Theocharis, A. D.; Karamanos, N. K. (Matrix BiolMatrix Biol, 2015)
The 17beta-estradiol (E2)/estrogen receptor alpha (ERalpha) signaling pathway is one of the most important pathways in hormone-dependent breast cancer. E2 plays pivotal roles in cancer cell growth, survival, and architecture as well as in gene expression regulatory mechanisms. In this study, we established stably transfected MCF-7 cells by knocking down the ERalpha gene (designated as MCF-7/SP10+ cells), using specific shRNA lentiviral particles, and compared them with the control cells (MCF-7/c). Interestingly, ERalpha silencing in MCF-7 cells strongly induced cellular phenotypic changes accompanied by significant changes in gene and protein expression of several markers typical of epithelial to mesenchymal transition (EMT). Notably, these cells exhibited enhanced cell proliferation, migration and invasion. Moreover, ERalpha suppression strongly affected the gene and protein expression of EGFR and HER2 receptor tyrosine kinases, and various extracellular matrix (ECM) effectors, including matrix metalloproteinases and their endogenous inhibitors (MMPs/TIMPs) and components of the plasminogen activation system. The action caused by E2 in MCF-7/c cells in the expression of HER2, MT1-MMP, MMP1, MMP9, uPA, tPA, and PAI-1 was abolished in MCF-7/SP10+ cells lacking ERalpha. These data suggested a regulatory role for the E2/ERalpha pathway in respect to the composition and activity of the extracellular proteolytic molecular network. Notably, loss of ERalpha promoted breast cancer cell migration and invasion by inducing changes in the expression levels of certain matrix macromolecules (especially uPA, tPA, PAI-1) through the EGFR-ERK signaling pathway. In conclusion, loss of ERalpha in breast cancer cells results in a potent EMT characterized by striking changes in the expression profile of specific matrix macromolecules highlighting the potential nodal role of matrix effectors in breast cancer endocrine resistance.
Keywords: *Epithelial-Mesenchymal Transition; breast cancer; Breast Neoplasms/genetics/metabolism/*pathology; Cell Movement; Cell Proliferation; EGFR; Epithelial to mesenchymal transition; estrogen receptor; Estrogen Receptor alpha/*genetics/metabolism; Extracellular Matrix/genetics/*metabolism; Female; Gene Expression Regulation, Neoplastic; Gene Knockdown Techniques; Humans; Invasion; Matrix metalloproteinases; MCF-7 Cells; Migration; tPA; uPA